2018
DOI: 10.1038/s41598-018-27921-0
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the characteristics, removal, and toxicity of effluent organic matter from a pharmaceutical wastewater treatment plant during catalytic ozonation

Abstract: Changes in the characteristics, removal efficiency, and toxicity of pharmaceutical effluent organic matter (EfOM) after catalytic ozonation were investigated in this study. After a 90-min treatment with a catalytic ozonation process (COP) in the presence of MnO2 ceramsite, the total organic carbon (TOC), UV254, colority, protein, and humic acid removal rates were 13.24%, 60.83%, 85.42%, 29.36% and 74.19%, respectively. The polysaccharide content increased by 12.73 mg/L during the COP for reaction times between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Among IWWs, effluents from pharmaceutical plants are considered a big source of environmental pollution (Zhan et al, 2019). In recent years much attention has been given to the degradation of pharmaceutical products (Asif et al, 2017;Zhao et al, 2019), but pharmaceutical WWs can present also a strong colorization (Wen et al, 2018). Many treatments for pharmaceuticals degradation have been developed, but only few of them have been tested for color removal and mostly on synthetic WWs.…”
Section: Introductionmentioning
confidence: 99%
“…Among IWWs, effluents from pharmaceutical plants are considered a big source of environmental pollution (Zhan et al, 2019). In recent years much attention has been given to the degradation of pharmaceutical products (Asif et al, 2017;Zhao et al, 2019), but pharmaceutical WWs can present also a strong colorization (Wen et al, 2018). Many treatments for pharmaceuticals degradation have been developed, but only few of them have been tested for color removal and mostly on synthetic WWs.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [10] observed fast degradation of butyl xanthate at high O 3 dosage of 145.59 mg/(min•L), but the O 3 utilization was not concerned. As the reagent concentration in flotation pulps is usually 10 −3 -10 −4 mol/L [27], the pollutant concentration in flotation effluents is much lower than that of pharmaceutical effluents and petrochemical wastewaters [28,29]. In ozonation, a lower concentration of organics usually leads to a declined O 3 decomposition rate, resulting in lower ozone utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Also, there is a wide scope of surface-functionalization of nanomaterials which may increase their catalytic affinity towards target compounds, enhancing chemical and environmental stability and promoting reuse [43]. Currently, the most exploited nanomaterials for wastewater treatments include nanostructured carbon based catalysts i.e., carbon nanotubes, graphene, graphene oxide, nano-adsorbents, metal oxides nanoparticles, nano-assisted advanced oxidation processes, and nanofiltration membranes [30,[44][45][46][47]. Moreover, the contemporary technologies also tested the blend characteristics of more than one nanomaterial for exhibiting multifacet properties in the resulting nanocomposites.…”
Section: Advanced Treatment Methods Using Nano-materialsmentioning
confidence: 99%